2014
DOI: 10.1186/1471-2180-14-59
|View full text |Cite
|
Sign up to set email alerts
|

Population analysis of Vibrio parahaemolyticus originating from different geographical regions demonstrates a high genetic diversity

Abstract: BackgroundVibrio parahaemolyticus is frequently isolated from environmental and seafood samples and associated with gastroenteritis outbreakes in American, European, Asian and African countries. To distinguish between different lineages of V. parahaemolyticus various genotyping techniques have been used, incl. multilocus sequence typing (MLST). Even though some studies have already applied MLST analysis to characterize V. parahaemolyticus strain sets, these studies have been restricted to specific geographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
(106 reference statements)
6
14
0
Order By: Relevance
“…The MLST method showed 76 STs, of which 51 (67.1%) STs were newly identified. Similar results were reported by Urmersbach et al (27), where 130 V. parahaemolyticus strains obtained from a marine environment were classified into 82 STs, and 82.9% of them were described as new. Rahman et al (28) also identified 63 unique STs in the isolates tested, and 49 (77.8%) STs were not described in the database.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The MLST method showed 76 STs, of which 51 (67.1%) STs were newly identified. Similar results were reported by Urmersbach et al (27), where 130 V. parahaemolyticus strains obtained from a marine environment were classified into 82 STs, and 82.9% of them were described as new. Rahman et al (28) also identified 63 unique STs in the isolates tested, and 49 (77.8%) STs were not described in the database.…”
Section: Discussionsupporting
confidence: 89%
“…It was also found that the largest PFGE 60 group, with 7 strains recovered mainly from clams in Italy, was resistant to ampicillin and streptomycin and belonged to ST481. This sequence type was previously identified in environmental isolates from Germany and Italy, as well as in clinical strains from China (27,28) (http://pubmlst.org/vparahaemolyticus). In the present study, ST481 was closely related to new ST1359 and ST1389 detected in V. parahaemolyticus from clams originating from Italy and the Netherlands, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…So translating the in-frame nucleotide sequences into peptide sequences allows a phylogenetic analysis based on pSTs. In this study, the assignment of pSTs of the analyzed isolates to CCs was carried out as previously (Theethakaew et al, 2013 ; Urmersbach et al, 2014 ) and predicted also by goeBURST algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…In the ME tree ( Fig. 2 ) published trh2 variants of Norway [ 36 ] and some more German isolates with trh genes [ 39 ] are displayed. Few trh negative strains with ST 121 and ST 761 were incorporated into the ME tree.…”
Section: Discussionmentioning
confidence: 99%